A prospective longitudinal multicentre study of health related quality of life in ICU survivors with COPD - Berkius, Johan (BioMed Central, 2013)
INTRODUCTION: Mortality amongst COPD patients treated on the ICU is high. Health-related quality of life (HRQL) after intensive care is a relevant concern for COPD patients, their families and providers of health care. Still, there are few HRQL studies after intensive care of this patient group. Our hypothesis was that HRQL of COPD patients treated on the ICU declines rapidly with time. METHODS: Fifty-one COPD patients (COPD-ICU group) with an ICU stay longer than 24 hours received a questionnaire at 6, 12 and 24 months after discharge from ICU. HRQL was measured using two generic instruments: the EuroQoL instrument (EQ-5D and EQ-VAS) and the Short Form 36 Health Survey (SF-36). The results were compared to HRQL of two reference groups from the general population; an age- and sex-adjusted reference population (Non-COPD reference) and a reference group with COPD (COPD reference). RESULTS: HRQL of the COPD-ICU group at 6 months after discharge from ICU was lower compared to the COPD reference group: Median EQ-5D was 0.66 vs. 0.73, P = 0.08 and median EQ-VAS was 50 vs.55, P < 0.05. There were no significant differences in the SF-36 dimensions between the COPD-ICU and COPD-reference groups, although the difference in physical functioning (PF) approached statistical significance (P = 0.059). Patients in the COPD-ICU group who were lost to follow-up after 6 months had low HRQL scores at 6 months. Scores for patients who died were generally lower compared to patients who failed to respond to the questionnaire. The PF and social functioning (SF) scores in those who died were significantly lower compared to patients with a complete follow up. HRQL of patients in the COPD-ICU group that survived a complete 24 months follow up was low but stable with no statistically significant decline from 6 to 24 months after ICU discharge. Their HRQL at 24 months was not significantly different from HRQL in the COPD reference group. CONCLUSIONS: HRQL in COPD survivors after intensive care was low but did not decline from 6 to 24 months after discharge from ICU. Furthermore, HRQL at 24 months was similar to patients with COPD who had not received ICU treatment.